Konstruksi Bina Damai terhadap Eks-Napiter (Studi Kasus pada Yayasan Lingkar Perdamayan Desa Tenggulun Kecamatan Solokuro Kabupaten Lamongan dalam Menangani Eks-Napiter) - Hadi Ismanto (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2022)
Terrorism that occurred in Indonesia is one of the social phenomena that causes unrest in our society. Like the Bali bombings (2002). The perpetrators have been sentenced by the Court. One of them is Amrozi, he has a large following, A small number of followers and is currently establishing the Circle of Peace Foundation. This foundation focuses on embracing and empowering ex-terrorist convicts (ex-convicts). The author is interested in researching the Peace Development Construction carried out by the Lingkar Peace Foundation for ex-convicts. This paper reveals another side of dealing with terrorism by building peace between governments, terrorists and the general public. The research method used by the author is qualitative, namely by direct observation and interviews with the management of the Lingkar Peace Foundation, as well as several ex-convicts.